METHODOLOGICAL FEATURES OF DISTANCE TEACHING OF PHYSICS - Кузнєцова, Олена (SWorldJournal, 2024)
First, the Covid-19 pandemic, and later a full-scale enemy invasion prompted the introduction of distance education in domestic higher education institutions. Existing information and communication technologies have provided a powerful educational environ